Space Vector PWM Algorithms for Three-level Inverter - Urmila Bandaru; Y. Sai Indira Priyadarshini; M. Siva Sathyanarayana (Advanced Aspects of Engineering Research Vol. 16, 2021)
Variable frequency and variable voltage are increasingly supplied by a three-level voltage source inverter for variable speed applications. The appropriate output voltage at the line side of the inverter is obtained using a suitable pulse width modulation technique. This chapter investigates the three-level Diode Clamped or Neutral Point Clamped topology, which is a popular multi-level topology. The modulation wave is generated using two Sine-triangle methods and two Space Vector Pulse Width Modulation methods. To produce the PWM signals for the three phases, these modulation waves are compared to a triangular carrier. Instead of the three phase modulating waves used in SPWM, a rotating reference voltage vector is used as a voltage reference in SVPWM methods. The magnitude and frequency of the line side’s fundamental variable are controlled by the magnitude and frequency of the reference vector, respectively. Because of its higher dc bus utilization and lower harmonic distortion than SPWM, Space Vector Modulation has become a common PWM technique for three-phase Voltage Source Inverters. In MATLAB/SIMULINK software, the four PWM methods are simulated and compared for THD and Capacitor Balance. Embedded Editor and Matlab Editor Functions are used to build the programs. As compared to Sine PWM, simulation results show that Space vector PWM better utilizes dc bus voltage, produces less THD, and improves capacitor balance.